Preliminary Study Needs Analysis Developing a Relevant and Effective Learning Model Design of Genetics Course - Lastiar Roselyna Sitompul; Robinson Situmorang; Cecep Kustandi; Reisky Tammu (Proceeding International Conference on Digital Education and Social Science, 2024)
Learning genetics courses often faces challenges because the material studied is abstract and complex. A relevant learning model is needed that meets the needs of students to improve their competence in genetics courses. This study aims to identify the needs of students and lecturers through a needs analysis approach as a basis for developing a relevant genetics learning model. The study used a qualitative descriptive method. Data were collected through interviews, questionnaires, and document observations. The results of the analysis showed that students needed learning that was more integrated with the context of everyday life to understand the concept of genetics in depth and needed motivational learning because this course was considered a difficult course. The lecturer explained the need to develop a learning model that provides interactive activities, such as project-based learning, case studies, or other effective strategies to improve student competence. Based on these results, a prototype of a contextual genetics learning model will be developed to meet the needs of students and lecturers teaching the course. These findings are the basis for designing a more relevant and effective genetics learning model. The study provides initial insight into the needs of genetics learning and is the first step in developing an effective learning model according to the context of students. Further research is needed to test and implement the proposed model